2023
DOI: 10.1002/ohn.320
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of an Expanded Targeted Early Cytomegalovirus Testing Program

Abstract: ObjectiveDetermine the detection rate from an expanded targeted early cytomegalovirus (CMV) testing program implemented from a large healthcare system (Intermountain Healthcare, IHC).Study DesignRetrospective review.SettingTertiary medical center.MethodsAn electronic system was modified to include indications for testing whenever a provider placed an order for CMV testing. A retrospective analysis of this database was performed.ResultsFrom March 1, 2021 to August 31, 2022, there were 3450 (8.8%) patients who u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 23 publications
3
12
0
Order By: Relevance
“…Based on these criteria, they found substantial rationale and evidence to support a hearing-targeted approach to testing for congenital CMV. Recently, Suarez et al reported that an expanded targeted early cCMV testing program can significantly improve detection rates compared to a more limited hearing-targeted early CMV program [ 19 ]. Testing was carried out for any newborn found to meet any of the following criteria: maternal history of CMV infection, idiopathic elevated liver enzymes or bilirubin, failed hearing screening, abnormal central nervous system imaging findings suggestive of cCMV, being small for gestational age, microcephaly, unexplained hepatosplenomegaly or petechial rash.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these criteria, they found substantial rationale and evidence to support a hearing-targeted approach to testing for congenital CMV. Recently, Suarez et al reported that an expanded targeted early cCMV testing program can significantly improve detection rates compared to a more limited hearing-targeted early CMV program [ 19 ]. Testing was carried out for any newborn found to meet any of the following criteria: maternal history of CMV infection, idiopathic elevated liver enzymes or bilirubin, failed hearing screening, abnormal central nervous system imaging findings suggestive of cCMV, being small for gestational age, microcephaly, unexplained hepatosplenomegaly or petechial rash.…”
Section: Discussionmentioning
confidence: 99%
“…Due to concerns with universal testing and the limitation of the HT-cCMV screening, expanded targeted cCMV protocols have been introduced. 27 Expanded targeted cCMV testing protocol recommends CMV testing for any newborn found to meet any of the following criteria: maternal history of CMV infection, idiopathic elevated liver enzymes or bilirubin, failed hearing screen, abnormal central nervous system imaging findings suggestive of cCMV (for example, intracranial calcifications), unexplained thrombocytopenia, history of intrauterine growth restriction, small for gestational age, macrocephaly, microcephaly, intra-abdominal calcifications, unexplained hepatomegaly or splenomegaly, or petechial rash. These expanded criteria help identify many symptomatic infants who would not be identified through the HT-cCMV screening protocols.…”
Section: Screening For Ccmvmentioning
confidence: 99%
“…Such programs have since implemented widely in the United States, Canada, the United Kingdom, Europe and Australia. The indications for testing later also explicitly included other signs of cCMV infection in the newborn period, such as thrombocytopenia, jaundice or microcephaly in some (“expanded”) targeted programs [32 ▪ ]. Although testing newborns with these abnormalities for cCMV could reasonably be considered to be simply an expectation of good clinical care rather than screening, it has been well documented that even newborns with symptomatic cCMV are rarely diagnosed without a formal screening program [17,33,34 ▪ ].…”
Section: Strategies Of Newborn Screening For Congenital Cytomegalovir...mentioning
confidence: 99%
“…Targeted screening identifies a large fraction of cases of SNHL due to cCMV and for which antiviral treatment is indicated [32 ▪ ,51 ▪ ,52]. Most hearing loss due to cCMV, however, is not detected by UNHS because it develops after birth, primarily during the first year, but anytime up to at least 5 years old [19].…”
Section: Arguments For and Against Newborn Screening For Congenital C...mentioning
confidence: 99%